Tradição legal, codificação e práticas institucionais : um relance pelo poder régio no Portugal de quatrocentos - Freitas, Judite A. Gonçalves de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The analysis of the public official letters of Book One of the Alfonsine Ordinances and of the Manueline Ordinances and the levels of application of the legislative principles there contained are the focus of this study. The law compiled refers to the existence of laws, titles and paragraphs whose source is not contemporary with the edition, building upon earlier information and legislative experience. Thus, one aims to highlight the process of organisation of the first compilations of Portuguese royal laws, and simultaneously unveil the degree of application of the legislated law in face of the practiced law, on the grounds of the administrative praxis of the different instances of Royal Power.